Merkel cell polyomavirus oncoproteins induce microRNAs that suppress multiple autophagy genes. Issue 6 (20th June 2019) - Kumar, Satendra; Xie, Hong; Shi, Hao; Gao, Jiwei; Juhlin, Carl Christofer; Björnhagen, Viveca; Höög, Anders; Lee, Linkiat; Larsson, Catharina; Lui, Weng‐Onn
Abstract : Viruses can inhibit host autophagy through multiple mechanisms, and evasion of autophagy plays an important role in immune suppression and viral oncogenesis. Merkel cell polyomavirus (MCPyV) T‐antigens are expressed and involved in the pathogenesis of a large proportion of Merkel cell carcinoma (MCC). Yet, how MCPyV induces tumorigenesis is not fully understood. Herein, we show that MCPyV T‐antigens induce miR‐375, miR‐30a‐3p and miR‐30a‐5p expressions, which target multiple key genes involved in autophagy, including ATG7, SQSTM1 (p62) and BECN1 . In MCC tumors, low expression of ATG7 and p62 are associated with MCPyV‐positive tumors. Ectopic expression of MCPyV small T‐antigen and truncated large T‐antigen (LT), but not the wild‐type LT, resulted in autophagy suppression, suggesting the importance of autophagy evasion in MCPyV‐mediated tumorigenesis. Torin‐1 treatment induced cell death, which was attenuated by autophagy inhibitor, but not pan‐caspase inhibitor, suggesting a potential role of autophagy in promoting cell death in MCC. Conceptually, our study shows that MCPyV oncoproteins suppress autophagy to protect cancer cells from cell death, which contribute to a better understanding of MCPyV‐mediated tumorigenesis and potential MCC treatment. Abstract : What's new? About four‐fifths of Merkel cell carcinomas harbor the Merkel cell polyomavirus (MCPyV) genome, though mutations in viral T antigens generally render MCPyV replication‐deficient. Here, the authors describe a network by which MCPyV oncoproteins and viral‐regulated miRNAs hijack autophagy machinery in MCC. In cells, expression of MCPyV T‐antigens induced miR‐375, miR‐30a‐3p, and miR‐30a‐5p expression. Subsequent experiments validated these miRNAs as autophagy regulators that specifically target the genes ATG7, SQSTM1, and BECN1 . Autophagy suppression protected MCC cell survival. This novel insight into the role of MCPyV and autophagy regulation in MCC may be relevant in the generation of future therapeutic strategies.